EFL LEARNERS’ LANGUAGE TRANSFER IN WRITING SHORT ENGLISH ESSAYS: A STUDY AT ENGLISH DEPARTEMENT OF UNP PADANG - Hermawati Syarif (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
Cross-linguistic influence within mutilingual users commonly happens when communication occurs. While using a forein language, for instance, learners  often transfer the first language to the foreign language.  The study at the English department UNP Padang shows how students transfer the Indonesian language in writing their short English essays. Linguistic and non-linguistic differences of the two languages are the factors discussed to see how the first language transfer emerged in their writing.  Through the analysis of 30 pieces of students’ short essay, it is found that students’ language transfer is  seen in  factors of linguistics, such as the structure of topic-prominent transfer and literal  translation, pragmatic (concentration progression on cohesion and coherence) and culture (indirectness and implicitness).